Norway : 2013 Article IV Consultation. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2013)
This 2013 Article IV Consultation highlights that Norwegian economy has been performing well, with mainland GDP growing steadily. However, the continuing buildup of assets in the sovereign wealth fund and the increasing share of the mainland economy that is supplying goods and services to the oil sector are leading to competitiveness pressures in other industries exposed to international competition. The IMF staff report suggests that inflation is expected to be below target for some time and gradually rise to the target in the medium term.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet